Innate immunity receptors in depression and suicide: upregulated NOD-like receptors containing pyrin (NLRPs) and hyperactive inflammasomes in the postmortem brains of people who were depressed and died by suicide - Pandey, Ghanshyam N.; Zhang, Hui; Sharma, Anuradha; Ren, Xinguo (Journal of psychiatry & neuroscience, 2021)
Abnormalities of inflammation have been implicated in the pathophysiology of depression and suicide, based on observations of increased levels of proinflammatory cytokines in the serum of people who were depressed and died by suicide. More recently, abnormalities in cytokines and innate immunity receptors such as toll-like receptors have also been observed in the postmortem brains of people who were depressed and died by suicide. In addition to toll-like receptors, another subfamily of innate immunity receptors known as NOD-like receptors containing pyrin (NLRPs) are the most widely present NOD-like receptors in the central nervous system. NLRPs also form inflammasomes that play an important role in brain function. We studied the role of NLRPs in depression and suicide. We determined the protein and mRNA expression of NLRP1, NLRP3 and NLRP6 and the components of their inflammasomes (i.e., adaptor molecule apoptosis-associated speck-like protein [ASC], caspase1, caspase3, interleukin [IL]-1β and IL-18) postmortem in the prefrontal cortex of people who were depressed and died by suicide, and in healthy controls. We determined mRNA levels using quantitative polymerase chain reaction, and we determined protein expression using Western blot immunolabelling. We found that the protein and mRNA expression levels of NLRP1, NLRP3, NLRP6, caspase3 and ASC were significantly increased in people who were depressed and died by suicide compared to healthy controls. Some people who were depressed and died by suicide were taking antidepressant medication at the time of their death. Similar to toll-like receptors, NLRP and its inflammasomes were upregulated in people who were depressed and died by suicide compared to healthy controls. Innate immunity receptors in general — and NLRPs and inflammasomes in particular — may play an important role in the pathophysiology of depression and suicide.